Calculation and Programming of Motion Coordinates for 5-axis Machining of Cubic B-splineinterpolating Surface - Li , Geng (International Journal of Mechanical and Electrical Engineering, 2025)
The control point of cubic B-spline interpolation surface is calculated inversely and the back cutter face is fitted according to the given profile value points. The movement coordinates of each axis of the five-axis grinding machine after the grinding wheel grinding are calculated. Using MATLAB software to draw the given original data, then calculate the μ-direction and ω-direction control points through the B-spline difference, and then generate the standard B-spline surface. According to the grinding principle of the five-axis grinding machine, coordinate changes are made, and finally the grinding track of the grinding wheel is calculated and visualized.